C-terminal provasopressin (copeptin) is associated with left ventricular dysfunction, remodelling and clinical heart failure in survivors of myocardial infarction. (22nd September 2015) - Kelly, D; Khan, SQ; Squire, IB; Quinn, P; Struck, J; Morgenthaler, NG; Davies, JE; Ng, LL
Abstract : Acute myocardial infarction (AMI) is associated with left ventricular dysfunction and clinical heart failure. Arginine vasopressin (AVP), also known as antidiuretic hormone, is a nonapeptide released from the hypothalamus, which promotes renal water conservation via the V2 receptor and hence influences osmoregulation and cardiovascular homeostasis. AVP is elevated in heart failure and post-myocardial infarction and is associated with adverse prognosis; however, its measurement in plasma is hampered by rapid clearance from the circulation and instability ex vivo. Copeptin, the C-terminal fragment of provasopressin is a 39 amino acid glycoprotein with a molecular mass of 5 kDa, which is secreted in equimolar amounts to vasopressin, is stable for several days after blood withdrawal and is hence more readily measured as a surrogate for AVP. The aim of this study was to describe the association between copeptin with left ventricular dysfunction, volumes, remodelling and clinical heart failure post-AMI. Methods: We studied 274 subjects with AMI. Copeptin was measured from plasma at discharge and subjects underwent echocardiography at discharge and follow-up (median 155 days). Subjects were followed for clinical heart failure for a median of 381 days. Remodelling was assessed as the change in left ventricular volumes between echo examinations. Results: Copeptin correlated directly with the wall motion index score (WMIS) and inversely with left ventricular ejection fraction (LVEF) at discharge (WMIS, r  =  0.276, p<0.001; LVEF, r  =  −0.188, p = 0.03) and follow-up (WMIS, r  =  0.244, p<0.001; LVEF, r  =  −0.270, p<0.001) and with ventricular volumes at follow-up (left ventricular end-diastolic volume, r  =  0.215, p = 0.002; left ventricular end-systolic volume (LVESV), r  =  0.299, p<0.001). Copeptin was associated with ventricular remodelling: change in end-diastolic volume, r  =  0.171, p = 0.015; change in end-systolic volume, r  =  0.186, p = 0.008. Subjects with increasing LVESV had higher levels of copeptin (median 6.30 vs 5.75 pmol/l, p = 0.012). Subjects with clinical heart failure (n  =  30) during follow-up had higher copeptin before discharge (median 13.55 vs 5.80 pmol/l, p<0.001). In a Cox proportional hazards model, copeptin retained its association with clinical heart failure (p = 0.032). Kaplan–Meier assessment revealed increased risk in subjects with copeptin greater than 6.31 pmol/l (odds ratio 5.26; 95% CI 2.07 to 13.3, log rank, p<0.001). Conclusion: Copeptin is associated with left ventricular dysfunction, volumes, remodelling and clinical heart failure post-AMI. Measurement of copeptin may provide prognostic information and the AVP system may be a therapeutic target in post-myocardial infarction left ventricular dysfunction.